Assessment of knowledge of healthcare workers in a service hospital regarding breastfeeding practices in mothers confirmed or suspected to have COVID-19 - Rajan, A R; Vishal, Anish Kumar; Bhave, Anupama Arvind (Indian Journal of Child Health, 2020)
Introduction: Breastfeeding is nature’s way of nurturing newborn and infants. Doubts exist among healthcare workers (HCWs) about the advice regarding breastfeeding to mothers who test positive/suspected for COVID-19. Objective: The objective of this study was to assess the knowledge among HCWs at a service hospital regarding breastfeeding among mothers suspected/confirmed for COVID-19. Materials and Methods: This was a hospital-based cross-sectional study. A total of 69 HCWs comprising female ward assistants, nursing assistants, nursing officers, and medical officers were included in the study. A predesigned questionnaire was used to obtain information after taking consent. Results: A total of 76.92% of female ward assistants, 57.14% of nursing assistants, 83.33% of nursing officers, and 75% of medical officers were aware that COVID-19 is not passed through breast milk. About 92.31% of female ward assistants, 71.43% nursing assistants, 80% nursing officers, and 58.33% medical officers knew that it is safe to give expressed breast milk from COVID-19 suspected/positive mothers. The hygiene recommendations for COVID-19 suspected/confirmed mother for breastfeeding were known to 92.31% of female ward assistants, 100% nursing assistants, 96.67% of nursing officers, and 100% of medical officers. Only 15.38% of female ward assistants, 35.71% nursing assistants, 50% of nursing officers, and 58.33% of medical officers knew not to give infant milk formula and recommended exclusive breastfeeding to a baby of COVID-19 suspected/confirmed mother. Conclusion: This study provides a foundation to focus on the promotion of optimal breastfeeding practices and creating awareness among HCWs about WHO guidance on breastfeeding during the COVID-19 pandemic.